Consumerism in the Modern Era: A Study of the Extravagant Verses in the Qur'an - Awadin, Adi Pratama; Yunus, Badruzzaman M.; Rusmana, Dadan; Ikhsan, Muhammad Jusuf Nur (Abdurrauf Journal of Islamic Studies, 2024)
In the Qur'an, the act of using property incorrectly is known as extravagant. This research aims to explain the causes that give birth to consumerism in the modern era, including the impact of industrialization, environmental factors, and the Qur'an's view of extravagant attitudes that affect consumerism. The researcher carried out this research by using a type of literature-based qualitative research through descriptive-analytical analysis. Research data comes from primary data and secondary data, where primary data is sourced from verses of the Qur'an about wastefulness, while secondary data is sourced from books, scientific articles, and research results. Researchers conduct data analysis by selecting data, collecting data, and making conclusions. The results of the study show that consumerism has been rampant in the modern era marked by the development of the industrial and technological world, technology has had a huge impact on the growth of people's lifestyles. Lifestyle takes place due to the influence of the environment and the self that desires happiness and pleasure. In the Qur'an, surah al-Isra' verses 26-27 explain that consumptive living or consumerism originates from living extravagantly, extravagant causes humans to be neglected from giving importance to desires rather than needs. Extravagant behavior is reflected in liking to squandering wealth on something that is not useful. Islam does not give freedom to its people in life without rules, regarding the consumption of Islam does not justify extravagant behavior. The waste committed by a person reflects that he is unable to control himself and has low faith. This study recommends conducting further research on case studies of consumerism that occurs in humanity that has an influence on environmental sustainability. [Di dalam al-Qur’an perbuatan yang menggunakan harta secara tidak benar dikenal dengan istilah boros. Penelitian ini bertujuan untuk memaparkan sebab-sebab yang melahirkan konsumerisme di era modern, termasuk dampak industrialisasi, faktor lingkungan, dan pandangan al-Qur’an mengenai sikap boros yang berpengaruh terhadap konsumerisme. Peneliti melaksanakan penelitian ini dengan mempergunakan jenis penelitian kualitatif berbasis kepustakaan melalui analisis secara deskriptif-analitis. Data penelitian berasal dari data primer dan data sekunder, di mana data primer bersumber dari ayat al-Qur’an tentang boros, adapun data sekunder bersumber dari buku, artikel ilmiah, dan hasil penelitian. Peneliti melakukan analisis data dengan memilih data, mengumpulkan data, dan membuat kesimpulan. Hasil penelitian menunjukkan bahwa konsumerisme telah merajalela di era modern yang ditandai semenjak perkembangan dunia industri dan teknologi, teknologi telah membawa dampak yang sangat besar bagi pertumbuhan gaya hidup masyarakat. Gaya hidup berlangsung disebabkan pengaruh lingkungan dan diri yang menginginkan kebahagian dan kesenangan. Pada al-Qur’an surat al-Isra’ ayat 26-27 dijelaskan bahwa hidup secara konsumtif atau konsumerisme berpangkal dari hidup secara boros, boros menyebabkan manusia terlalaikan dari mementingkan keinginan daripada kebutuhan. Perilaku boros tercermin dari kesukaan kepada menghambur-hamburkan harta kepada sesuatu yang tidak bermanfaat. Islam tidak memberikan keleluasaan kepada umatnya dalam kehidupan tanpa adanya aturan, perihal konsumsi Islam tidak membenarkan perilaku boros. Pemborosan yang dilakukan oleh seseorang mencerminkan bahwa dirinya sedang tidak mampu mengontrol diri dan rendahnya keimanan. Penelitian ini merekomendasikan untuk melakukan penelitian lebih lanjut mengenai studi kasus konsumerisme yang terjadi pada umat manusia yang memiliki pengaruh terhadap keberlangsungan lingkungan hidup].